If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (x + -5) * 2 + 16 Reorder the terms: y = (-5 + x) * 2 + 16 Reorder the terms for easier multiplication: y = 2(-5 + x) + 16 y = (-5 * 2 + x * 2) + 16 y = (-10 + 2x) + 16 Reorder the terms: y = -10 + 16 + 2x Combine like terms: -10 + 16 = 6 y = 6 + 2x Solving y = 6 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 6 + 2x
| -x+16=-32 | | 10=2s+2 | | 6x-4(3x)+12=103-x | | 19=6+33t+-16t^2 | | D^4+D^2+4D+4=0 | | (4x-1)=56 | | 2(m-21)+4(m-3)=48 | | (7x+2)=(3x+-2) | | -3-m=-3 | | 2/3x-3=1/2x+4 | | 5g+10=3g+21 | | 5x+4=4x+8 | | 11p-4s+5r-3p+2s-r= | | -1w+4=3 | | 5x-42=3x+6 | | -7+u=-2 | | 4x+15=2x+6 | | -18=-3w | | 2(x+4)=6+x | | -1v+3=11 | | 5a+6b=-23 | | 3-3d=-3 | | 11-2z=1 | | 2(x-22)+3(x-3)=37 | | 173-v=284 | | 2x-9y-6x-8y+7z= | | 250+10=90b+12 | | 5=4p-11 | | 7d+14e= | | 2(2w-3)-8w= | | m=6/5,(8,-2) | | 5x+7=67-x |